Religious Commitment and its Relation to Happiness among Muslim Students: The Educational Level as Moderator - Achour, Meguellati (Journal of religion and health, 2017)
This study examines the relationship between religiosity and level of happiness in an Islamic context among Muslim students studying at Malaysian universities. The determinants of happiness included in this research are positive attitudes, self-esteem, and other-esteem. Religiosity has long been considered as the main determinant in increasing happiness, and educational level strengthens its relationship. For this purpose, the researchers sampled 230 Muslim students aged 17-40 years studying at Malaysian universities in Kuala Lumpur, Malaysia. The study found a positive and significant correlation between religious commitment and level of happiness. Religious commitment also shows positive and significant correlations with positive attitudes, self-esteem, and other-esteem. The study also concludes that educational attainment moderates the relationship between religious commitment and happiness. Thus, religious commitment plays a very important role in increasing levels of happiness.